CORRELATION CONSTITUTIONAL PARAMETERS OF A BODY IN PRACTICALLY HEALTHY WOMEN OF MIDDLE INTERMEDIATE SOMATOTYPES WITH RHEOENCEPHALOGRAPHY INDICATORS - Serebrennikova, О.А.; Semenchenko, V.V.; Dmytrenko, S.V.; Semenenko, A.I.; Ocheretna, O.L.; Maievskyi, О.Ye.; Shayuk, А.V. (World of Medicine and Biology, 2018)
In practically healthy women from Podillia with middle intermediate somatotype, among the correlations of cerebral blood flow with anthropo-somatotypological parameters of the body, the highest percentage, mostly direct, reliable and unreliable connections of mean strength is established with the amplitude rheoencephalography parameters. Among the direct reliable and generally the average strength of the false correlations of time and derivative of the rheoencephalography parameters with constitutional parameters of the body, attention is drawn to the emergence of strong ties with time indices and an increase in the percentage of inverse relationships with the derivatives of the rheoencephalography parameters. In analyzing the correlations of different groups of anthropo-somatotypological parameters of the body with the parameters of cerebral circulation, it was established that the amplitude indexes have the highest relative percentage of connections with total, longitudinal, circumflex sizes and cephalometric indices; time indices - with the width of distal epiphyses of long tubular bones of the limbs and circumflexion dimensions; derivative indicators - with total, longitudinal dimensions, body diameters and width of distal epiphyses of long tubular bones of the extremities.
Keywords: cerebral hemodynamics; anthropometric indices; practically healthy women